Development and clinical implementation of a digital system for risk assessments for radiation therapy - Kornek, Dominik; Menichelli, David; Leske, Jörg; Hofmann, Michael; Antkiewicz, David; Brandt, Tobias; Ott, Oliver; Lotter, Michael; Lang-Welzenbach, Marga; Fietkau, Rainer; Bert, Christoph (Zeitschrift für Medizinische Physik, 2023)
Before introducing new treatment techniques, an investigation of hazards due to unintentional radiation exposures is a reasonable activity for proactively increasing patient safety. As dedicated software is scarce, we developed a tool for risk assessment to design a quality management program based on best practice methods, i.e., process mapping, failure modes and effects analysis and fault tree analysis. Implemented as a web database application, a single dataset was used to describe the treatment process and its failure modes. The design of the system and dataset allowed failure modes to be represented both visually as fault trees and in a tabular form. Following the commissioning of the software for our department, previously conducted risk assessments were migrated to the new system after being fully re-assessed which revealed a shift in risk priorities. Furthermore, a weighting factor was investigated to bring risk levels of the migrated assessments into perspective. The compensation did not affect high priorities but did re-prioritize in the midrange of the ranking. We conclude that the tool is suitable to conduct multiple risk assessments and concomitantly keep track of the overall quality management activities.
CRIS-Team Scopus Importer:2023-09-15
Keywords: Failure modes and effects analysis (FMEA); Fault tree analysis (FTA); Process throughput; Radiation therapy; Risk analysis; Risk-based quality management